Politics and Indigenous Victimization: the Case of Brazil - Carvalho, Salo de (The British journal of criminology, 2021)
There is a dearth of criminological scholarship on how the political persuasions of governments affect Indigenous people as it relates to human rights and environmental consequences, whether positive or negative, for Indigenous peoples. To address this gap, we develop a comparative instrumental case study of the policies concerning Indigenous peoples implemented during two political periods in Brazil: the administrations of presidents Silva (2003-2010) and Rousseff (2011-2016) and the administrations of Temer (2016-2018) and Bolsonaro (2019-). We explore the consequences for Indigenous peoples of these leftist and the right-wing governments. We argue that governments of both political leanings victimize Indigenous populations, with leftist governments using structural violence and right-wing governments engaging additionally in symbolic and direct violence.